(untitled) (Bangladesh Journal of Otorhinolaryngology, 2016)
Objective: To find out the relation of conductive hearing loss in children with enlarged adenoids. Methods: Study was conducted in out patients department and Indoor wards of the Department of Otolaryngology on Head Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka during the periods of October 2005 to March 2006. 60 patients with enlarged amides were included in this study. The assessment of the patients were established on the basic of history clinical, 2 and audiological examination was done. Data were collected and analyzed using statistical package for Social Science. Results: In this study 60 patients (from 3 years to 12 years age) diagnosed as having enlarged adenoids in the Otolaryngology and Head-Neck Surgery out patient and in patient Departments of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from May 2005 to March 2006 are included in this series. Most of the patients presented with multiple symptoms, the commonest was the hearing impairment (58.33%). Other common symptoms were mouth breathing (50.00%), Nasal obstruction (50.00%), snoring (46.67%). Majority of them were male (62.85%) and 53.33% were in the 5-10 years age group. Middle class family occupy the lion share (58.33%). 60.00% patients live in a overcrowded condition. 50.00% patients were found with gross enlargement of adenoids. Hearing impairment was found in 58.33% ears of-patients of adenoids. Reduced middle ear pressure and compliance were found in 64.00% ears. Among the patients of enlarged adenoids otitis media with effusion was found in 58.33% (35) of patients. Among the patients of OME majority was male (62.85%). There was 77.14% (27) bilateral and 22.85% (8) unilateral cases. On otoscopy of OME patients, all patients had retraction of tympanic membrane, cone of lights were distorted in 50.00%, fluidlevels in 68.57% and bubbles were in 28.57% of ears. 71.43% OME patients had hearing loss in the range of 26-40 dB. Middle ear pressure and compliance were found reduced in 88.57% (62) ears of OME patients. There were 58.33% incidence of OME among enlarged adenoids cases. All the patients of OME with enlarged adenoids had a hearing loss between 26-55dB. Out of the 22 OME cases with gross adenoids, 16 had a middle ear pressure between -201 to-300 mm of H20 and 19 had a middle ear pressure between -101 to -200 mm of H20. On myringotomy fluid came out from all 62 (100%) ears. From majority (38) ears serous type of fluid came out. Conclusion: This is an endeavor to find out a correlation of enlarged adenoids with conductive hearing impairment in children. Otitis media with effusion is suspected in all children suffering from enlarged adenoids. All together 60 patients with enlarged adenoids were included in the study. Result of this study may not be the actual picture of overall situation due to many limitations is this study. Still it can be concluded that enlarged adenoids has a definite role in causing OME and conductive hearing impairment. So early diagnosis and treatment of enlarged adenoids can be encouraged to decrease the actual incidence, morbidity and complications of otitis media with effusion and thus conductive hearing impairment in childhood. Bangladesh J Otorhinolaryngol; October 2015; 21(2): 62-68